2003
DOI: 10.1002/cncr.11553
|View full text |Cite
|
Sign up to set email alerts
|

Levels of the soluble, 55‐kilodalton isoform of tumor necrosis factor receptor in bone marrow are correlated with the clinical outcome of children with acute lymphoblastic leukemia in first recurrence

Abstract: BACKGROUNDIt has been shown that the soluble, 55‐kilodalton isoform of tumor necrosis factor receptor (sTNFRp55) enhances tumor survival by exhibiting competitive ligand binding. The objective of the current study was to determine the levels of sTNFRp55 and their impact on outcome in 106 children with acute lymphoblastic leukemia (ALL) in first recurrence.METHODSBetween January 1997 and December 2001, bone marrow (BM) samples were collected from 106 children with a first recurrence of ALL at diagnosis. These p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Although TNF can signal through two receptors, TNFR1 and TNFR2, the majority of TNF-mediated biological events are mediated via TNFR1 signaling (Chen and Goeddel, 2002; Locksley et al ., 2001; MacEwan, 2002; Tartaglia and Goeddel, 1992; Vandenabeele et al ., 1995). Furthermore, TNFR1 plays an important role in the induction of several cancers (Arnott et al ., 2004; Figueras et al , 2005; Houtenbos et al , 2004; Lind et al ., 2004; Wu et al , 2003). TNFα and TNFR1 have been linked to UVR carcinogenesis (Moore et al , 1999; Suganuma et al , 1999; Starcher, 2000; Wheeler et al , 2004; Wheeler et al , 2005; Zhuang et al , 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Although TNF can signal through two receptors, TNFR1 and TNFR2, the majority of TNF-mediated biological events are mediated via TNFR1 signaling (Chen and Goeddel, 2002; Locksley et al ., 2001; MacEwan, 2002; Tartaglia and Goeddel, 1992; Vandenabeele et al ., 1995). Furthermore, TNFR1 plays an important role in the induction of several cancers (Arnott et al ., 2004; Figueras et al , 2005; Houtenbos et al , 2004; Lind et al ., 2004; Wu et al , 2003). TNFα and TNFR1 have been linked to UVR carcinogenesis (Moore et al , 1999; Suganuma et al , 1999; Starcher, 2000; Wheeler et al , 2004; Wheeler et al , 2005; Zhuang et al , 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Although treatment has improved drastically over the past few decades, approximately 20–25% of paediatric patients with ALL still experience disease relapse [ 17 , 18 ]. Recent studies have shown that aberrant expression of cytokines and their receptors in the tumour microenvironment contributes to clonal expansion of transformed lymphoid precursor cells, thus promoting the progression of leukaemia [ 5 , 19–21 ]. IL-33 has been shown to participate in different biological activities in both nonhematological and hematological malignancies [ 22–25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In consonance with observations in other disease patterns, inflammatory microenvironment might prospectively promulgate leukaemia immune escape. Recent studies have demonstrated that abnormal expression of cytokines and/or activation of their receptors contribute to the onset and progression in several haematopoietic malignancies [ 5 , 6 ]. The expression of commonly studied cytokines such as vascular endothelial growth factor (VEGF), IL-6, and IL-10, were found to correlate with the outcomes of patients with chronic lymphocytic leukaemia (CLL), thus indicating the benefit of using cytokines as biomarkers for treatment efficacy monitoring [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…CD74 plays an important role in multiple myeloma and its higher expression induces tumor cell malignancy [13]. An isoform of the tumor necrosis factor TNFRSF1A is associated with the development of Acute Lymphoblastic Leukemia (ALL) in children [14]. Specifically, LCN2 has been found to be connected with Acute Myelogenous Leukemia (AML) [15].…”
Section: Methodsmentioning
confidence: 99%